Proposals for a reformed European asylum and migration policy - Clara Albrecht; Yvonne Giesing; Panu Poutvaara; Elitsa Stefanova (CESifo GmbH, 2024)
The weaknesses of the Common European Asylum System have led to conflicts of interest between the EU's external border states and the main destination countries, such as Germany. After years of negotiations, the reform of the European asylum policy was formally adopted by the European Parliament in April 2024. It introduces an accelerated procedure in order to speed up the asylum application process, especially in terms of rejecting applications deemed to be unjustified. However, it does not address one of the main problems: the lack of legal ways for low-skilled people who are migrating for economic reasons.
Keywords: 330